Sociologija nesreč in COVID-19 - Špitalar, Maruša (Družboslovne razprave, 2021)
Natural disasters (predominantly those linked to meteorological and geophysical changes) prevail among studies performed in the field of the sociology of disasters, therefore the same parameters may be used while analysing social dynamics due to COVID-19. The specificity of its nature might cause an even higher level of fear and damage (non-material) than other types of disaster. The article will address deviances in society due to the disruption brought by epidemic through the lens of the sociology of disasters and Enrico Quarantelli's concepts of social phenomena and social construction. The main parameters used in the analysis of natural disasters are described (vulnerability, exposure, response) and how the latter can be insightful while addressing social dynamics.
Keywords: Covid-19; družbena konstrukcija nesreče; Epidemics; Epidemije; exposure; izpostavljenost; Naravne nesreče; Natural disasters; ranljivost; social construction; Sociologija; sociologija nesreč; Sociology; sociology of disasters; vulnerability